1987
DOI: 10.1161/01.cir.76.3.618
|View full text |Cite
|
Sign up to set email alerts
|

Causes of failure and pathologic findings in surgically removed Ionescu-Shiley standard bovine pericardial heart valve bioprostheses: emphasis on progressive structural deterioration.

Abstract: Twenty-three lonescu-Shiley standard bovine pericardial bioprostheses (15 aortic, seven mitral, and one tricuspid) removed at surgery from 21 adults, 28 to 75 years old (mean 55 at reoperation), were examined after functioning for as long as 84 months (mean 26 BIOPROSTHESES fabricated from glutaraldehydepretreated porcine aortic valves or bovine pericardium are commonly used to replace diseased human cardiac valves. Primary tissue degeneration due to intrinsic cuspal calcification is the most frequent cause of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(56 citation statements)
references
References 30 publications
3
53
0
Order By: Relevance
“…Butany et al [28] in their study of 24 explanted ISLP and others [26,30] observed that primary tissue failure and tears were the predominant mode of failure in ISLP. This was followed by infective endocarditis, thrombus, paravalvular leak, and pannus overgrowth ( Figure 9).…”
Section: Modes Of Failurementioning
confidence: 99%
See 4 more Smart Citations
“…Butany et al [28] in their study of 24 explanted ISLP and others [26,30] observed that primary tissue failure and tears were the predominant mode of failure in ISLP. This was followed by infective endocarditis, thrombus, paravalvular leak, and pannus overgrowth ( Figure 9).…”
Section: Modes Of Failurementioning
confidence: 99%
“…It had a commissural suture ("alignment suture"), through-and-through stitch at the top of the cusps at each stent post, to hold the adjacent cusps together at the stent (site of highest compressive stress) and to align the cusp free margins with one another. This valve had good hemodynamics but failed prematurely due to factors related to its design, that is, abrasion-related damage at the alignment suture [26].…”
Section: Ionescu-shiley Standard (Iss)mentioning
confidence: 99%
See 3 more Smart Citations